2014
DOI: 10.1016/j.cell.2014.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeletal Tension Inhibits Hippo Signaling through an Ajuba-Warts Complex

Abstract: Mechanical forces have been proposed to modulate organ growth, but a molecular mechanism that links them to growth regulation in vivo has been lacking. We report that increasing tension within the cytoskeleton increases Drosophila wing growth, whereas decreasing cytoskeletal tension decreases wing growth. These changes in growth can be accounted for by changes in the activity of Yorkie, a transcription factor regulated by the Hippo pathway. The influence of myosin activity on Yorkie depends genetically on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

38
454
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 324 publications
(513 citation statements)
references
References 66 publications
38
454
2
1
Order By: Relevance
“…Yki activity is down-regulated through phosphorylation by the Warts (Wts) kinase, which promotes cytoplasmic localization of Yki. Wts is regulated in several ways, including phosphorylation by Hippo (7), regulation of Wts abundance (8), regulation of Wts localization (9,10), and regulation of Wts interaction with cofactors and inhibitors (11)(12)(13)(14)(15). We recently defined a mechanism for biomechanical regulation of Hippo signaling in which cytoskeletal tension induces recruitment of Ajuba LIM protein (Jub) to α-catenin, and thence recruitment of Wts to Jub (11).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Yki activity is down-regulated through phosphorylation by the Warts (Wts) kinase, which promotes cytoplasmic localization of Yki. Wts is regulated in several ways, including phosphorylation by Hippo (7), regulation of Wts abundance (8), regulation of Wts localization (9,10), and regulation of Wts interaction with cofactors and inhibitors (11)(12)(13)(14)(15). We recently defined a mechanism for biomechanical regulation of Hippo signaling in which cytoskeletal tension induces recruitment of Ajuba LIM protein (Jub) to α-catenin, and thence recruitment of Wts to Jub (11).…”
mentioning
confidence: 99%
“…We recently defined a mechanism for biomechanical regulation of Hippo signaling in which cytoskeletal tension induces recruitment of Ajuba LIM protein (Jub) to α-catenin, and thence recruitment of Wts to Jub (11). Jub is an inhibitor of Wts (12,13), and this tension-dependent corecruitment of Jub and Wts to adherens junctions is associated with reduced Wts activity, and hence increased Yki activity (11), at least in part because it prevents Wts from moving to sites where Wts gets activated (9). Conversely, under conditions of lower cytoskeletal tension, recruitment of Wts and Jub to adherens junctions is decreased, Wts activity is increased, and consequently Yki activity is decreased.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A similar study has been performed in Caenorhabditis elegans zygotes in which actomyosin meshwork was ablated and the initial outward velocity of adjacent cortex was proportional to cortical tension (39). In separate studies, we know cytoskeleton tension is tightly connected to the Hippo-Yes-associated protein pathway that controls cell proliferation and organ growth (40)(41)(42). With the advance in genetically encoded, ratiometric biosensors for cell signaling proteins (43), there is some exciting potential in investigating how the distribution of tensile load by optical ablation could modulate spatial signaling.…”
Section: Optical Ablation Of Intracellular Structuresmentioning
confidence: 76%
“…Previous work showed that YAP functions in a mechanosensitive pathway and responds to increased tension, extracellular matrix stiffness, and cell spreading (Dupont et al, 2011;Rauskolb et al, 2014;Swift et al, 2013). These and other data suggest YAP may act in a positive feedback loop where tension stimulates YAP activation, and YAP responds by increasing tissue tension (Calvo et al, 2013).…”
mentioning
confidence: 88%